Research and Application of Computer Aided Analysis and Optimization Algorithm for Fault Tree - Liu, Chao (Proceedings of the The 1st EAI International Conference on Multimedia Technology and Enhanced Learning, 2016)
This paper describes the computer aided fault tree analysis principle, the fault tree of main parameters (minimum cut sets, the minimal path sets and disjoint minimal cut sets, the minimum path set between the transformation rules, achieved by cut set, path set compared with each other by fault tree qualitative analysis algorithm and the direct no cross is used to realize the quantitative analysis of the fault tree of the new algorithm. The reasonable application of these new algorithms can effectively reduce the difficulty of NP FTA, and provide a new way for the simplification of FTA. With C++ language in the VC development environment developed a fault tree qualitative and quantitative analysis of computational program components, and developed a set of FTA analysis software based on this component. This software has applied the theory of optimization algorithm, which has the main functions of the minimum cut set and the minimal path set calculation, the calculation of availability, the importance calculation and the fault diagnosis based on fault tree. In fact we use the higher order arrays reducing dimension technology and dynamic numerical method, when complete the calculation function of a dynamic array, immediately release the memory space occupied by, faster to meet the demand of computer for large fault tree analysis. Through the fault analysis of some fault trees and the comparison with other software, it is proved that the optimization algorithm and the application software are scientific and effective. Finally, through the further research on the specific application of the optimization algorithm and the software in the field of safety evaluation and fault diagnosis, it shows that the optimization algorithm and the software has a good practical value in engineering.